2022
DOI: 10.1038/s41419-022-04542-0
|View full text |Cite
|
Sign up to set email alerts
|

LINC01123 promotes immune escape by sponging miR-214-3p to regulate B7–H3 in head and neck squamous-cell carcinoma

Abstract: Numerous studies have shown that long noncoding RNAs (LncRNAs) are involved in the development and immune escape of head and neck squamous-cell carcinoma (HNSCC). However, the specific regulatory mechanisms by which LINC01123 regulates HNSCC and its correlation with immunity remain unclear. Therefore, this study’s primary purpose was to explore the mechanisms by which LINC01123 regulates the immune escape and progression of HNSCC. This study confirmed that LINC01123 is competitively bound to miR-214-3p, and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Second, we focused on the roles of circWDR62 in TMZ resistance and malignant progression. More detailed studies are necessary to explore the role of circWDR62 in other biological behaviours of glioma, including immune escape and tumour energy metabolism [ 53 ]. In addition, the upstream regulatory mechanism of circWDR62 in TMZ-resistant glioma cells and tissues also worthy of further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we focused on the roles of circWDR62 in TMZ resistance and malignant progression. More detailed studies are necessary to explore the role of circWDR62 in other biological behaviours of glioma, including immune escape and tumour energy metabolism [ 53 ]. In addition, the upstream regulatory mechanism of circWDR62 in TMZ-resistant glioma cells and tissues also worthy of further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are rare consistent prognostic biomarkers for HNSCC due to high heterogeneous genomics and complex etiology ( Beck and Golemis, 2016 ; Yang et al, 2020 ). Studies have revealed that lncRNAs hold potential in the pathogenesis, diagnosis, prognosis, and targeted treatment of patients with HNSCC by promoting DNA damage and regulating the cell cycle ( Guglas et al, 2017 ; Wang Y. et al, 2020 ; Jiang et al, 2022 ; Li et al, 2022 ), while the role of GI-associated with lncRNAs in the prediction of TIME and therapeutics for HNSCC has not been systematically assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Ritu Chaudhary et al found that LINC00460 was abundant in HNSCC tissue and associated with poor patient survival ( Chaudhary et al, 2020 ). Several lncRNA-based signatures showed prognostic effect ( Liu G. et al, 2018 ; Wang et al, 2021 ) and correlated with TIME landscape ( Cao et al, 2022 ; Li et al, 2022 ). However, rare studies have reported GI-related lncRNAs potentials in predicting TIME and therapies in HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…35 Studies have reported that B7-H3 is highly expressed in HNSCC, blocking the expression of B7-H3 reduces the recruitment of MDSCs and M2-TAMs in the tumor microenvironment and promotes the activation of T cells, and enhances the antitumor immune response. 36,37 The receptor of scavenger receptor type B-1(SCARB1) expressed on MDSCs cells is highly affinitive for high-density lipoprotein (HDL), and synthetic high-density lipoprotein nanoparticles (HDL-NP) specifically bind to this receptor. In a mouse melanoma model, HDL-NP binding to SCARB1 attenuated immunosuppression and activated T cell-mediated immune responses, which reduced tumor growth and improved survival in mice.…”
Section: Myeloid-derived Suppressing Cells (Mdscs) Are the Major Immu...mentioning
confidence: 99%
“…The expression of B7‐H3 protein is low in normal human tissues such as the prostate, breast, placenta, liver, colon, and lymphoid organs 35 . Studies have reported that B7‐H3 is highly expressed in HNSCC, blocking the expression of B7‐H3 reduces the recruitment of MDSCs and M2‐TAMs in the tumor microenvironment and promotes the activation of T cells, and enhances the antitumor immune response 36,37 . The receptor of scavenger receptor type B‐1(SCARB1) expressed on MDSCs cells is highly affinitive for high‐density lipoprotein (HDL), and synthetic high‐density lipoprotein nanoparticles (HDL‐NP) specifically bind to this receptor.…”
Section: Immune Cells Involved In Tumor Immunologymentioning
confidence: 99%